Integrated Mineral Analysis of sandstone and dolomite formations using different chelating agents during matrix acidizing - Shafiq, M.; Ben Mahmud, Hisham; Ghasemi, M. (2018)
© 2018 Southwest Petroleum University Mineral analysis plays a major role in the successful matrix acidizing as it shows the change in physiochemical changes in the formation due to the reaction with fluids injected. Mineralogy of the reservoir can be altered by injecting mineral acids during matrix acidizing. But various complications are connected during the application of these acids such as environmental hazards, corrosion of pipes and tubings, precipitation of fluosilicates and fast spending of acid. To mitigate these problems, chelating agents have been applied as an alternative by different researchers. In this study, three different chelating agents EDTA, GLDA and HEDTA were applied to stimulate sandstone and dolomite samples. The pH value of these chelates ranges from 1.7 to 3 and is measured before and after core flooding to observe physiochemical changes. Core flooding experiments under 180 °F temperature were performed at a constant flow rate of 1 ml/min on core samples having dimensions (3 inch × 1.5 inch). Porosity, permeability, Inductively Coupled Plasma (ICP), and TESCAN Integrated Mineral Analysis (TIMA) were employed to measure changes in formation properties such as morphology, topology and mineralogy. The reacted sample of acids was analyzed for sodium, potassium, calcium, aluminium, magnesium, and iron using the ICP technique to find the capability of these chelates to remove positive ions. HEDTA found to be effective in chelating iron, calcium and magnesium and it also removed some amount of aluminium ions from the sandstone samples. Permeability and porosity analysis concluded that HEDTA is more efficient in creating new big pore spaces. TIMA analysis confirms that HEDTA is effective in dissolving quartz and other positive ions while dissolved a large amount of calcium and sodium from the sandstone as compared to other chelates. TIMA analysis also concluded that HEDTA is effective in increasing porosity of sandstone formation while GLDA is effective in dolomites.